A simulation–based equipment environment for flexible manufacturing systems. (9th January 2012) - Huang, Yi–Sheng; Chiang, Ho–Shan
This paper discusses a new simulation environment that provides a cell controller to coordinate equipment within a cell to perform a sequence of manufacturing operations. Petri net models mapping to scenario–based simulators of the equipment are described. The intended advantage of the simulation environment is that only one personal computer can make all experimental tests and does not need the actual manufacturing equipment. We start with the tool of scenario to model the operation sequences of the system's equipment. The scenario methodology is able to depict clearly the signals of communication for the equipment. Finally, two examples are proposed for the simulation environment.